2000
DOI: 10.1086/501787
|View full text |Cite
|
Sign up to set email alerts
|

Association of Antibiotic Utilization Measures and Control of Multiple-Drug Resistance inKlebsiella pneumoniae

Abstract: Antibiotic-use measures may be particularly important for control of MDR K. pneumoniae, whether emergence is clonal or polyclonal.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
69
1
2

Year Published

2005
2005
2017
2017

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 140 publications
(73 citation statements)
references
References 12 publications
1
69
1
2
Order By: Relevance
“…Some authors have suggested that use of ␤-lactam/␤-lactamase inhibitor combinations, rather than cephalosporins, as workhorse empirical therapy for infections suspected as being due to gram-negative bacilli, may facilitate control of ESBL producers (296,311,341). The mechanism by which these drugs may reduce infections with ESBL producers is not certain.…”
Section: Infection Control When Esbl-producing Organisms Are Already mentioning
confidence: 99%
“…Some authors have suggested that use of ␤-lactam/␤-lactamase inhibitor combinations, rather than cephalosporins, as workhorse empirical therapy for infections suspected as being due to gram-negative bacilli, may facilitate control of ESBL producers (296,311,341). The mechanism by which these drugs may reduce infections with ESBL producers is not certain.…”
Section: Infection Control When Esbl-producing Organisms Are Already mentioning
confidence: 99%
“…(16,43,215,216,323,355,365). While the mechanism for decreasing ESBL-producing isolates is not clear, it must be noted that the efficacy of ␤-lactam-␤-lactamase inhibitor combinations may be reduced for organisms VOL.…”
Section: ␤-Lactamase Inhibitors In Clinical Practicementioning
confidence: 99%
“…The use of certain classes of antimicrobials, such as 3rd-generation cephalosporins is implicated in the development of resistance caused by enzymes in the group of ESBLs [4][5][6] . Restriction of such drugs causes a reduction in the incidence of these beta-lactamases in hospitals [4,6] .…”
Section: Introductionmentioning
confidence: 99%